PVDF-CLOISITE hollow fiber membrane for CO2 absorption via membrane contactor - Izzati, Ahmad Rudaini; Rosmawati, Naim; Sureena, Abdullah; N. M., Mohktar; Juhana, Jaafar (Penerbit Universiti Teknologi Malaysia, 2017)
The effect of cloisite concentrations on CO2 absorption via polyvinylidene fluoride-cloisite hollow fiber in membrane contactor system was investigated. PVDF polymer was modified by introducing different compositions of cloisite clay (S1: 0%, S2:1 wt%, S3: 3 wt% and S4: 5 wt%) into the polymer solution. The hollow fiber membranes were examined via liquid entry pressure (LEPw), contact angle and scanning electron microscope (SEM). CO2 absorption test was conducted at different liquid absorbent flow rates of 1M MEA. S4 gives highest Liquid entry pressure value and S3 obtained highest contact angle value at around 87.21º. Different concentrations of cloisite exhibited various finger-like structure with sponge-like morphology on the membrane lumen side. Meanwhile, the highest CO2 absorption flux of 3.41×10-2 mol/m2.s at flowrate of 200 ml/min was obtained for membrane S4. Long term performance for membrane S4 up to 55 hours of CO2 absorption showed increasing absorption trend up to 6.78 ×10-2 mol/m2.s of CO2 fluxes.